Developing knowledge and value in management consulting - Buono, Anthony F. (Research in management consulting, 2002)
The second volume in the Research in Management Consulting series focuses on developing knowledge and value in management consulting. While there has been an exponential explosion in both the presence and role played by management consultants, the exact nature of their contribution --to client organizations, to our understanding of management and organization, to our comprehension of the increasingly complex dynamics associated with business in a global marketplace, and to the development of their own firms--remains ambiguous. Just as the business world is experiencing rapid and, at times, volatile change, the consulting industry itself is also facing unprecedented change and challenge. Over the next decade, forecasts suggest a world of difference for management consulting, from different competitors and different types of projects and assignments, to different skill sets and different fee structures, to different client expectations.